Bank stock price volatility in Indonesia: The impact of monetary policy, macroeconomic factors, global factors, and bank characteristics - Yuyun Yuningsih; Cep Jandi Anwar; Deswita Herlina (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study aims to examine the influence of monetary policy, macroeconomic factors, global factors, and bank characteristics on the volatility of banking stock returns in Indonesia. Design/methodology/approach – Using a quantitative explanatory approach, the study analyzes quarterly panel data from 40 banks listed on the Indonesia Stock Exchange during the period 2020Q1–2024Q4, selected through purposive sampling based on data completeness. The analysis employs a dynamic panel regression model with the System Generalized Method of Moments (GMM) to address endogeneity and capture dynamic relationships among variables. Findings – The findings reveal that the BI Rate and LIBOR have a positive and significant effect on stock return volatility, indicating that changes in domestic and global interest rates increase market uncertainty. In contrast, exchange rate stability, inflation, and the Dow Jones Index are found to reduce volatility. From the perspective of bank characteristics, total assets and the Capital Adequacy Ratio (CAR) decrease volatility, while Return on Assets (ROA) increases it. Research limitations – The study is limited to the banking sector within a specific post-pandemic period and does not incorporate non-economic factors such as investor sentiment or governance variables. Implications – Academically, this study enriches the literature on banking stock volatility in developing countries by demonstrating the simultaneous role of monetary, global, and bank characteristics. Future research could expand the model by incorporating variables such as market sentiment, fiscal policy, or governance indicators. Practically, these findings emphasize the importance of monetary policy coordination and strengthening bank capital in maintaining stock market stability, and provide empirical references for investors in managing banking stock risk.